PERSIMPANGAN DILEMA PENANGANAN PENGUNGSI ASING DI INDONESIA PASCA PENERBITAN PERPRES NO. 125 TAHUN 2016 - Agung Priambodo (Universitas Bina Sarana Informatika, 2021)
This article aims to unravel the issues of the threat of waves of refugees and asylum seekers in Indonesia. The concept of non-traditional security is adopted in this study as a framework for analyzing social problems of refugees and asylum seekers that have an impact on national security and interests. This research uses descriptive-qualitative analysis method to draw a common thread of threats that may arise along with the implementation of Presidential Decree no. 125 of 2016 concerning Handling of Refugees from Overseas. Referring to the results of data analysis, this study draws four reasons for the possible consequences of the wave of refugees in Indonesia, including: the regulations in Presidential Decree no. 125 of 2016 with other laws and regulations, the dilemma of unlimited stay permits, and the lack of budget allocations for sustainable handling of refugees.